If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-6=2(x-1)=x
We move all terms to the left:
4x-6-(2(x-1))=0
We calculate terms in parentheses: -(2(x-1)), so:We get rid of parentheses
2(x-1)
We multiply parentheses
2x-2
Back to the equation:
-(2x-2)
4x-2x+2-6=0
We add all the numbers together, and all the variables
2x-4=0
We move all terms containing x to the left, all other terms to the right
2x=4
x=4/2
x=2
| 6c+14=+4c | | 9-5x=12-(6x+7 | | 5+3+-2+-4=c | | -15/4=-5y | | 6/5=-3h/8 | | 8y+4=2(y-1) | | c+39=4c | | 4n-8=68 | | b-5+7b=20 | | 15x-2=55x+2 | | 3/8(8x+16)+1=1/2(8x-2)+1 | | 5^x+1=125 | | -5x/4=35 | | 199t-5-3=7.5 | | Y=x/3-9 | | ,5x+1=125 | | -14x-20=-13x+50= | | -33+(-7)=29+n | | 5x+7+7x=-8+3x | | -3(1-5k)=8(1+2k) | | x+.05x=27000 | | 3x-7=11* | | 4=6/8+x | | 1=7+4s | | 35+128+x=180 | | 0.7x–1.4=–3.5 | | a÷(-8)+15=23 | | 4+2x=8* | | 4^3n=32 | | 126+6x=180 | | 52+55+x=180 | | 31+x=92 |